How does India’s rural roads program affect the grassroots? : findings from a survey in upland Orissa - Bell, Clive (Land economics, 2014)
This paper analyzes the effects of all weather rural roads on households’ net output prices, education, and health in a poor region of India. Cross-section and before-and-after comparisons yield these findings: (1) net output prices were 5% or more higher; (2) fewer days of schooling were lost due to bad weather, largely because teachers had fewer absences; (3) the acutely sick received timelier treatment and more frequently in a hospital than the nearest primary clinic; and (4) respondents ranked the resulting benefits in the domains of health and education at least as highly as the “commercial” ones. (JEL O12, O18)